Parametric Analysis of Laser Machining with Response Surface Method on SS-304. (2016) - Kotadiya, D.J.; Pandya, D.H.
Abstract: Stainless steel is an important engineering material that is difficult to be cut by oxy-fuel methods because of the high melting point and low viscosity of the formed oxides. However, it is suitable to be cut by laser. The objective of this work is to do parametric analysis of process parameters of CO2 laser cutting system on surface characteristics of the cut section in the cutting of 5 mm Stainless Steel (SS) sheet (ASTM 304). In this study, the laser cutting parameters such as laser power, cutting speed and gas pressure are analyzed and optimized with consideration of workpiece surface roughness. Design of experiments (DOE), ANOVA and Response Surface Methodology (RSM) approaches are used to analyze the laser cutting variables and find out the optimum value for surface roughness. By analyzing, it is observed that the laser power has more effect on responses rather than cutting speed and gas pressure. It is clearly shown that the above performance characteristics in laser cutting process can be optimized effectively through this approach.